2018
DOI: 10.3390/en11010204
|View full text |Cite
|
Sign up to set email alerts
|

Performance Study of a Cylindrical Parabolic Concentrating Solar Water Heater with Nail Type Twisted Tape Inserts in the Copper Absorber Tube

Abstract: This paper reports the overall thermal performance of a cylindrical parabolic concentrating solar water heater (CPCSWH) with inserting nail type twisted tape (NTT) in the copper absorber tube for the nail twist pitch ratios, 4.787, 6.914 and 9.042, respectively. The experiments are conducted for a constant volumetric water flow rate and during the time period 9:00 a.m. to 15:00 p.m. The useful heat gain, hourly solar energy collected and hourly solar energy stored in this solar water heater were found to be hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
(25 reference statements)
0
13
0
1
Order By: Relevance
“…The use of flow water heaters has been discussed in many studies in the world [6,7,8,9,10,11,12,13] and from an energy point of view in for example [10,13,14,15,16]. Flow water heaters are compact in size and provide a constant supply of hot water for as long as necessary.…”
Section: Tankless Flow Water Heaters Versus Storage Tank Water Heatersmentioning
confidence: 99%
“…The use of flow water heaters has been discussed in many studies in the world [6,7,8,9,10,11,12,13] and from an energy point of view in for example [10,13,14,15,16]. Flow water heaters are compact in size and provide a constant supply of hot water for as long as necessary.…”
Section: Tankless Flow Water Heaters Versus Storage Tank Water Heatersmentioning
confidence: 99%
“…Tokgoz et al [22] numerically studied the heat transfer rate increment in a corrugated duct considering Al2O3/water nanofluid as heat transfer fluid. Bhakta et al [23] experimentally investigated the performance parameters of a CPC fitted with nailed twisted tape in an absorber tube.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous ideas have been examined in thermal and hydraulic studies. Generally, every study investigated only one method, while there are only two comparative studies [10,48]. In this direction, this paper is a comparative study among three usual thermal enhancement methods of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Too and Benito [10] compared the use of dimpled absorber tube, as well as the use of twisted tape inserts and the use of coil inserts. They found that the dimpled absorber tube is the best case among the examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation